Preparing cationic dyeable polyamide 6 filaments by combining the masterbatch technique with melt copolymerization. Issue 3 (February 2022) - Zhang, Shengming; Wu, Yuhao; Yang, Hanbin; Ji, Peng; Wang, Chaosheng; Wang, Huaping; Yan, Zhiyong
Cationic dyeable polyamide 6 (CD-PA6) fiber, as a novel functional polyamide 6 (PA6) fiber, conforms to people's requirements for fashion clothing. However, due to the limitation of the hetero-end groups after caprolactam hydrolysis, it is difficult to introduce comonomers into the PA6 molecular chain to prepare PA6-based polymers with a certain molecular weight and maintain the original physical properties and spinnability. In this paper, through molecular design of PA6 segments, 5-sulfoisophthalic acid monosodium salt (5-SSIPA) was introduced into PA6 by copolymerization, and a CD-PA6 masterbatch with an addition amount of 10 wt% was prepared. CD-PA6 were prepared by blending with pure PA6 with masterbatch technology. The melt-spinning method was used to prepare CD-PA6 filaments, and they were woven into fabrics. The results show that the CD-PA6 masterbatch and PA6 have good blending compatibility. CD-PA6 filaments and fabrics maintain the excellent physical properties of PA6. When the addition amount of 5-SSIPA is 3%, the dye uptake rate of the cationic pigment exceeds 90%, and it has color affinity and excellent color fastness.